Urgensi Sex Education untuk Anak Usia Dini di Zaman Modern - Muhammad Shaleh Mahfuzh; Juliana Batubara; Nurfarida Deliani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Early childhood (0-6 years) is considered a critical period that determines adolescent and adult development. This phase shows a process of change that includes growth, development, maturity, and perfection, both physically and mentally, which takes place throughout life in successive stages. Therefore, providing beneficial education to children at an early age is natural and important to prepare them for the future. One important aspect of educating children at an early age is sex education. The aim of this approach is to provide information and help children understand how to safeguard and protect their bodies from potential harm. This research uses a literature study method with a qualitative approach, relying on secondary data sources such as books, journals, articles and related publications. The results of this study show that sex education involves conveying information and forming attitudes related to sex, gender, gender identity, inter-gender relations, and other intimate aspects. The importance of providing sex education from an early age is to provide children with an understanding of how to safeguard and protect their bodies from potential harm.